Dendrobium taprobanium (Orchidaceae): a new species from Sri Lanka with taxonomic notes on some species of the genus - Priyadarshana, Tharaka Sudesh; Atthanagoda, Anusha Gayan; Wijewardhane, Ishara Harshajith; Aberathna, Nimantha; Peabotuwage, Indika; Kumar, Pankaj (Phytotaxa, 2020)
A new species, Dendrobium taprobanium (Orchidaceae), is described and illustrated from the Sabaragamuwa Province in Sri Lanka. The new species is morphologically similar to D. trinervium from Indochina. However, it can be readily distinguished by having a rounded callus with fine glandular hairs at the seam of the hypochile and epichile, while D. trinervium has three rows of thickened glabrous calli arising from the middle or posterior end of the lip and extending to the apex of the midlobe. Due to its morphological similarities, D. gunnarii, an endemic orchid from the Andaman Islands, India, is synonymised to D. trinervium. Additionally, taxonomic notes are also provided for D. heterocarpum, D. macrostaychum and D. nutantiflorum, and a lectotype is designated for D. panduratum. A key to all the Dendrobium species in Sri Lanka is provided along with colour photographs.